Pressure-Volume (PV) Diagrams plotting, using Cubic Equations of States (EOS), for pure substance, and some thermodynamic properties calculations - BENCHINE Noussaiba; MECHEMACHE Khadidja; BOUREZG Mohammed Tahar (My University, 2025)
: VLE is a fundamental concept in thermodynamics and chemical engineering. PR and SRK EOS are employed, to model such behavior, for Ethylene, a light hydrocarbon that plays a vital role in the petrochemical industry. Our research is focused on evaluating EOS performance in predicting key thermodynamic properties, specifically, saturation pressure, molar volumes, across a range of temperatures. Another key property investigated in this work is the enthalpy of vaporization (ΔHvap). To answer this, we analyze and compare the EOS predictions against experimental data (NIST). The comparative results indicate that, Both models offer reasonable accuracy in predicting the vap–liq behavior under subcritical conditions, especially at lower temperatures. SRK, while simpler in form and computationally more efficient, exhibits increasing deviation at higher P &T . Its predictions for are reasonably accurate at lower temperatures but tend to drift at elevated thermodynamic states. PR consistently yields predictions closer to experimental values across all T ranges. It shows a better fit in both vapor and liquid phase molar volumes, and provides superior estimations of enthalpy of vaporization. The evidence clearly supports the PR EOS as more robust and reliable model. Its improved formulation yields lower prediction errors and better alignment with experimental data across a wide temperature range
MAJOR: Chemical Engineering